Effect of the crystallinity of diamond coatings on cemented carbide inserts on their cutting performance in milling. Issue 1 (2019) - Skordaris, G.; Bouzakis, K.-D.; Kotsanis, T.; Boumpakis, A.; Stergioudi, F.; Christofilos, D.; Lemmer, O.; Kölker, W.; Woda, M.
Abstract: Micro-crystalline diamond (MCD) coatings were deposited on cemented carbide inserts at different temperatures using hot filament chemical vapor deposition technique. For investigating the effect of the developed diamond crystallinity on the fatigue strength and wear behaviour of the prepared MCD coated inserts, inclined impact tests and milling investigations were conducted correspondingly. Raman spectra were recorded for capturing the crystalline phases after the film deposition and their potential changes after the impact and milling experiments induced by the mechanical and thermal loads. Thus, the explanation of the cutting performance of the employed diamond coated inserts with various crystalline phases was enabled.